2015
DOI: 10.3892/or.2015.3767
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2D- and 3D-culture models as drug-testing platforms in breast cancer

Abstract: It is becoming recognized that screening of oncology drugs on a platform using two-dimensionally (2D)-cultured cell lines is unable to precisely select clinically active drugs; therefore three-dimensional (3D)-culture systems are emerging and show potential for better simulating the in vivo tumor microenvironment. The purpose of this study was to reveal the differential effects of chemotherapeutic drugs between 2D- and 3D-cultures and to explore their underlying mechanisms. We evaluated differences between 2D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
488
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(564 citation statements)
references
References 25 publications
(38 reference statements)
36
488
2
2
Order By: Relevance
“…This may be a primary reason as to why results of anticancer drug assessments using MCTS are more predictive of clinical efficacy than 2D cell assessments (Carver et al, 2014). Many antineoplastic agents have been reported to be less effective for cancer cells cultured in 3D than 2D (Frankel et al, 2000;Imamura et al, 2015;Karlsson et al, 2012). The architectural structure of MCTS is the main reason for this difference.…”
Section: Why 3d Culture?mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be a primary reason as to why results of anticancer drug assessments using MCTS are more predictive of clinical efficacy than 2D cell assessments (Carver et al, 2014). Many antineoplastic agents have been reported to be less effective for cancer cells cultured in 3D than 2D (Frankel et al, 2000;Imamura et al, 2015;Karlsson et al, 2012). The architectural structure of MCTS is the main reason for this difference.…”
Section: Why 3d Culture?mentioning
confidence: 99%
“…Secondly, the tightly adhered cells and ECM in MCTS can limit drug penetration (Frankel et al, 2000). Moreover, the hypoxic core generates a G0-dormant cell population which is highly resistant to chemotherapy (Imamura et al, 2015). Gene expression of cells cultured in 3D systems differs from that of cells in 2D monolayer; for instance, expression of genes related to chemoresistance has been found to vary from 3D versus 2D systems (Lin and Chang, 2008).…”
Section: Why 3d Culture?mentioning
confidence: 99%
“…Foam-based 3D culture similar to fiber scaffolds [16] increased the resistance of the leukaemia cell lines to inhibitory effects of imatinib and to the maintenance of AML cells [29,30] and also selects bortezomib-resistant CML stem cells [31]. It has been shown that 3D-cultures are better than 2D-cultures in simulating important tumor characteristics in vivo such as hypoxia and resulting drug resistant phenotype [32]. The mechanism of resistance might also be due to poor access of drugs to the cells hidden in the niche like spaces in the scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…Retention in 3D structure, establishment of cell-cell contacts, and presence of extracellular matrix (ECM) are important reasons for spheroidal aggregation [16][17][18] . Currently, cell spheroids are used extensively in the study of tissue anatomy, drug screening [19,20] , toxicology [21] , and cell proliferation and differentiation [22,23] because they represent more similar in vivo biological behaviors. Therefore, cell spheroids could be an alternative format of the bioink.…”
Section: Introductionmentioning
confidence: 99%